2010
DOI: 10.1089/dia.2009.0115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Technosphere Inhaled Insulin on Quality of Life and Treatment Satisfaction

Abstract: In this study treatment with inhaled Technosphere insulin was well tolerated, clinically efficacious, and associated with positive patient-reported outcomes, including improved attitudes toward insulin therapy and high treatment satisfaction. This treatment strategy was implemented without a negative impact on health-related quality of life or worries about diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…6 Our finding of greater between-treatment arm differences in improvement for treatment satisfaction and diabetesspecific quality of life (fear of hypoglycemia) than for generic HRQOL is consistent with previous reports of other diabetes treatments. 20,21 We know of no other study comparing SAPT and MDI + SMBG that assessed HRQOL, but there have been studies of pump therapy and of CGM that assessed HRQOL. A recently published article by the Juvenile Diabetes Research Foundation CGM Study Group of children using insulin pump or MDI therapy reported findings similar to those of the current study; after 26 weeks SF-12 PCS and MCS scores (in adults) and PedsQL total scores (in children and caregivers) were largely unchanged in both CGM and SMBG treatment groups, with no significant difference between treatment groups except for a greater improvement in adult CGM patients in SF-12 PCS scores.…”
Section: Discussionmentioning
confidence: 99%
“…6 Our finding of greater between-treatment arm differences in improvement for treatment satisfaction and diabetesspecific quality of life (fear of hypoglycemia) than for generic HRQOL is consistent with previous reports of other diabetes treatments. 20,21 We know of no other study comparing SAPT and MDI + SMBG that assessed HRQOL, but there have been studies of pump therapy and of CGM that assessed HRQOL. A recently published article by the Juvenile Diabetes Research Foundation CGM Study Group of children using insulin pump or MDI therapy reported findings similar to those of the current study; after 26 weeks SF-12 PCS and MCS scores (in adults) and PedsQL total scores (in children and caregivers) were largely unchanged in both CGM and SMBG treatment groups, with no significant difference between treatment groups except for a greater improvement in adult CGM patients in SF-12 PCS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with TI was associated with high treatment satisfaction and improved attitudes toward insulin treatment [20], without a negative effect on health-related quality of life (HR-QOL) [8]. In trial 102 (Sect.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%
“…These barriers are seen to contribute to clinical inertia, a failure to start or intensify treatment in a timely manner [23]. Inhaled insulin may help to overcome these barriers [20]. TI (Afrezza Ò ) is currently the only inhaled insulin approved and marketed in the USA, and evaluations are ongoing for commercialization globally [10,11,24].…”
Section: Current Status Of Insulin Human Inhalation Powder In Type 1 mentioning
confidence: 99%
“…Considering the issues associated with Exubera in the past, patient satisfaction and acceptance has been evaluated with the new inhaled insulin product. Overall, significant improvements in attitudes toward insulin therapy, treatment satisfaction, and treatment preference were reported with Technosphere™ insulin (105,116). The therapeutical approach using the new inhaled insulin was implemented without a negative impact on health-related quality of life (116).…”
Section: Current Ultrafast Insulin Formulationsmentioning
confidence: 99%
“…Overall, significant improvements in attitudes toward insulin therapy, treatment satisfaction, and treatment preference were reported with Technosphere™ insulin (105,116). The therapeutical approach using the new inhaled insulin was implemented without a negative impact on health-related quality of life (116). To date, Technosphere™ insulin has demonstrated a favorable safety and tolerability profile in clinical studies that collected data in healthy volunteers and patients with diabetes (105).…”
Section: Current Ultrafast Insulin Formulationsmentioning
confidence: 99%